A Consensus Decision-Making Model considering Empathetic Preferences and Power Structure of the Poverty Alleviation E-Commerce Supply Chain - Ruili Shi; Lianming Zhao; Chunxiang Guo; Xin Gu (Complexity)
This article focuses on the conflict consultation process and empathetic decision-making behavior of a poverty alleviation supply chain composed of farmers, retailers, and third-party e-commerce platforms (e-platforms), and proposes an empathetic preference-based consensus decision-making model. The impact of empathetic preferences and power structure on the consensus reaching process are analyzed. The results indicate that consumers’ empathy increases the consensus wholesale price and sales price of products, while retailers’ and e-platforms’ empathy increase the wholesale price and reduce the sales price of products. The empathetic preferences of consumers, retailers, and e-platforms are helpful for increasing the profits of farmers. The retailer’s empathetic preference is not beneficial to its own profits and the supply chain, while the e-platform’s empathetic preference can help to improve its own income and increase the overall profit of the supply chain at first, before decreasing. Moreover, the power of retailer is positively correlated with the profits of farmers and the retailer, and negatively correlated with the profits of the e-platform and supply chain. The sales price and commission price are negatively correlated with the power of retailer, but the wholesale price is not related to the change in power structure.